Protein aggregate-ligand binding assays based on microfluidic diffusional separation - Zhang, Y; Buell, A; Müller, T; De Genst, E; Benesch, J; Dobson, C; Knowles, T (Wiley, 2016)
The measurement of molecular interactions with pathological protein aggregates, including amyloid fibrils, is of central importance in the context of the development of diagnostic and therapeutic strategies against protein misfolding disorders. Probing such interactions by conventional methods can, however, be challenging because of the supramolecular nature of protein aggregates, their heterogeneity, and their often dynamic nature. Here we demonstrate that direct measurement of diffusion on a microfluidic platform enables the determination of affinity and kinetics data for ligand binding to amyloid fibrils in solution. This method yields rapid binding information from only microlitres of sample, and is therefore a powerful technique for identifying and characterising molecular species with potential therapeutic or diagnostic application.